Impact of Androgens on Inflammation-Related Lipid Mediator Biosynthesis in Innate Immune Cells - Pace, Simona; Werz, Oliver (Frontiers in Immunology, 2020)
Rheumatoid arthritis, asthma, allergic rhinitis and many other disorders related to an aberrant immune response have a higher incidence and severity in women than in men. Emerging evidences from scientific studies indicate that the activity of the immune system is superior in females and that androgens may act as “immunosuppressive” molecules with inhibitory effects on inflammatory reactions. Among the multiple factors that contribute to the inflammatory response, lipid mediators (LM), produced from polyunsaturated fatty acids, represent a class of bioactive small molecules with pivotal roles in the onset, maintenance and resolution of inflammation. LM encompass pro-inflammatory eicosanoids and specialized pro-resolving mediators (SPM) that coexist in a tightly regulated balance necessary for the return to homeostasis. Innate immune cells including neutrophils, monocytes and macrophages possess high capacities to generate distinct LM. In the last decades it became more and more evident that sex represents an important variable in the regulation of inflammation where sex hormones play crucial roles. Recent findings showed that the biosynthesis of inflammation-related LM is sex-biased and that androgens impact LM formation with consequences not only for pathophysiology but also for pharmacotherapy. Here, we review the modulation of the inflammatory response by sex and androgens with a specific focus on LM pathways. In particular, we highlight the impact of androgens on the biosynthetic pathway of inflammation-related eicosanoids in innate immune cells.